PELAKSANAAN PEMBELAJARAN DARING KOLABORATIF PENGEMBANGAN KURIKULUM DAN PEMBELAJARAN SEKOLAH DASAR - Ratri Nuryani Qudwatullathifah; Gregorius Sebo Bito; Dede Hasanah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
Pembelajaran Daring Kolaboratif programmes are learning models that combine learning using technology. This learning approach relies on the use of information and communication technology (ICT) to support students in interacting and collaborating as the learning process of teaching takes place. The aim of this study is to evaluate student perceptions related to the Pembelajaran Daring Kolaboratif (PDK) Pengembangan Kurikulum dan Pembelajaran SD program in several aspects, such as learning models, the quality of teachers, and the educational institutions involved. This research uses qualitative method. Research subjects of 31 students who are involved in the PDK Pengembangan Kurikulum dan Pembelajaran SD program. The test instrument in research is a questionnaire. Study results showed that students' perception of PDK Pengembangan Kurikulum dan Pembelajaran SD, 92% was successfully established, 92% students accepted that the Learning Management System (LMS) learning model made it easier for students to access information about lectures.